Peripartum interventions resulting in reduced perinatal mortality rates, and birth asphyxia rates, over 18 years in a tertiary centre in South India: a retrospective study. (9th August 2019) - Ebenezer, ED; Londhe, V; Rathore, S; Benjamin, S; Ross, B; Jeyaseelan, L; Mathews, JE
Abstract : Objective: To study the changes in the rates of perinatal mortality, birth asphyxia, and caesarean sections in relation to interventions implemented over the past 18 years, in a tertiary centre in South India. Design: Retrospective study. Setting: Labour and maternity unit of a tertiary centre in South India. Population or sample: Women who gave birth between 2000 and 2018. Methods: Information from perinatal audits, chart reviews, and data retrieved from the electronic database were used. Interventions implemented during this time period were audits and training, obstetric re‐organisation, and minor changes in staffing and infrastructure. Main outcome measures: Main outcome measures were perinatal mortality rate, birth asphyxia rate, and caesarean section rate. Results: Perinatal mortality rate decreased from 44 per 1000 births in 2000 to 16.4 per 1000 births in 2018 ( P  < 0.001). The rates of babies born with birth asphyxia requiring admission to the neonatal unit decreased from 24 per 1000 births in 2001 to 0.7 per 1000 births in 2018 ( P  < 0.00001). The overall caesarean section rate was maintained close to 30%. Conclusion: In a large tertiary hospital in South India, with 14 000 deliveries per year, a policy of rigorous audits of stillbirths and birth asphyxia, electronic fetal monitoring, and the introduction of standardised criteria for trial of scar, reduced the perinatal mortality and the rate of babies born with birth asphyxia over the past 18 years, without an increase in the caesarean section rate. Tweetable abstract: Rigorous perinatal audits with training in fetal cardiotocography, decreased birth asphyxia, without a major increase in caesarean rates. Tweetable abstract: Rigorous perinatal audits with training in fetal cardiotocography, decreased birth asphyxia, without a major increase in caesarean rates.